Phyto Chemical Screening of Identification of Some Compounds from Neem Toddy - Sathiyaseelan, V.; Velauthamurty, K. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Azadirechta indica is commonly known as Vembu or neem tree and belonging to family meliaceae. Every part of the above plant - bark, root bark, young fruit, seed, flowers, leaves and the secretionmaterials such as gum and toddy are also medicinal value. It is a native medicinal plant in Sri Lanka. Parts of the neem tree is administered internally and externally in various forms such as decoction, juice, herbal wine, paste, tablets and medicated oils in the treatment. The objective of the study is screening of identification of some compounds of Neem toddy. Neem toddy is collected in the sterilised bottle from the matured neem tree in Meesalai. It is naturally secreted in sap wood of the neem tree. The bottled sample was sent to the chemistry laboratory at the Department of Chemistry, University of Jaffna for the standards phyto chemical screening and qualitative identification of alcohol, ketone, aldehyde, aromatic acid, ester, phenol, alkene, primary amine and aromatic nitro compounds. From the qualitative analysis it is concluded that the, primary alcohol, ketone, aromatic acid, ester and primary ammine were found in the sample. The presence of above mention chemical compounds in neem toddy may increase the immunity of the body.
Keywords: Neem toddy; Compounds; Primary ammine